Administrative and legal regulation of attorney-client privilege - Lavriv, Vitalii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article is devoted to the issue of administrative and legal regulation regarding the observance of attorney-client privilege in Ukraine. The author of the article focuses on a comparative legal analysis of the legislation of Ukraine and foreign countries, highlighting important differences and common aspects.The article examines the legal aspects related to the application of lawyer's secrecy in carrying out professional legal activities. The author of the article analyzes the practical aspects of solving problems, the concept and content of attorney confidentiality, the legal basis for resolving legal conflicts, the legislative regulation of attorney confidentialityThis article is an important contribution to the study of the problems of advocacy, as the legal nature of attorney secrecy is determined based on the analysis of legal acts and scientific sources, which made it possible to identify gaps in the legislation, develop and propose directions for development and ways to improve the current legislation of Ukraine, which is regulated application of lawyer's secrecy in Ukraine.